Ibuprofen gargle for chemo- or Chemoradiotherapy-induced Oral Mucositis: a feasibility study - Takeshi Ioroi; Naomi Kiyota; Yoshinori Imamura; Masaaki Tanda; Shiori Aoki; Mamoru Okuno; Kazuhiro Yamamoto; Ryohei Sasaki; Ken-ichi Nibu; Hironobu Minami; Midori Hirai; Ikuko Yano (BMC, 2020)
Abstract Background Oral mucositis frequently occurs in cancer patients treated with chemotherapy and chemoradiotherapy (CRT). This study examined the safety and efficacy of ibuprofen gargle in healthy volunteers and patients with chemotherapy- and concomitant CRT-induced oral mucositis. Methods We enrolled healthy volunteers and patients with chemotherapy- and CRT-induced oral mucositis. In cohort I, single and multiple doses of ibuprofen gargle (0.6% or 1.0%) were administered to healthy volunteers on day 1 and days 4-10. In cohort II, multiple doses of ibuprofen gargle (0.6%) were administered to patients with complicated grade 2-3 oral mucositis based on the Common Terminology Criteria for Adverse Events (CTCAE) version 4.0. The primary endpoint of cohort I was the treatment-related adverse events (TRAEs) as defined by CTCAE version 4.0. The primary endpoint of cohort II was the change in the visual analogue scale (VAS) pain score from before to 15 min after gargle use on day 3. The incidence and severity of TRAEs were assessed based on the CTCAE version 4.0 and a subjective rating scale completed by healthy volunteers and patients. Results In cohort I, 9 of 10 healthy volunteers were evaluable for safety. All 9 healthy volunteers reported the TRAE of oral irritation with single or multiple use of the gargle. In cohort II, 10 patients were enrolled and evaluable for safety and 7 of 10 patients were evaluable for efficacy. The mean change in the VAS pain score from before to 15 min after using the gargle on day 3 was − 1.28 (95% confidence interval: − 2.06, − 0.51), and all patients experienced some degree of pain relief (range: − 0.2 to − 2.5). All 10 patients reported the TRAE of oral irritation. No other TRAEs of ibuprofen gargle were observed in the healthy volunteers and patients. Conclusion Despite oral irritation, the ibuprofen gargle appeared to be safe and effective for the pain related to chemo- or CRT-induced oral mucositis. However, ibuprofen-related oral irritation warrants further formulation improvement. Trial registration This study was registered with the University Hospital Medical Information Network Clinical Trials Registry ( UMIN000014433 ).